‘I am from Busia!’ : everyday trading and health service provision at the Kenya-Uganda border as place-making activities - Allen, W (Routledge, 2013)
Critical researchers in anthropology, politics, and history have profited from the spatial turn, or the idea that spaces produced through practices and perceptions influence observable social action, in showing how people at borders derive specific economic and social benefits from their unique location. This is especially relevant in African border contexts where state presence is often modified or resisted by local agendas. However, less work examines how cross-border activities, locally-held perceptions, and geographic location interact to generate different versions of what it means to ‘be at’ a border for border-crossers and residents themselves. This paper, in responding to calls for interdisciplinary and multiperspectival approaches to border studies, argues that theorizing border towns as dynamic ‘places’ clarifies how individuals impact and construct different meanings at and across borders. It empirically develops this idea by examining two spheres of everyday activity occurring at the Kenya-Uganda border: cross-border trade and health service provision.